Ambivalence in grief therapy: The interplay between change and self-stability. Issue 2 (7th February 2016) - Alves, Daniela; Fernández-Navarro, Pablo; Ribeiro, António P.; Ribeiro, Eugénia; Sousa, Inês; Gonçalves, Miguel M.
ABSTRACT: This article explores the role of ambivalence in grief therapy within a narrative framework. From this perspective, change starts with the occurrence of innovative moments, which can be nullified by reaffirmation of the problematic self-narrative as a sign of ambivalence. This study analyzed ambivalence in six complicated grief cases using the "Return to the Problem Coding System." Markers of ambivalence emerged in all cases, with a decreasing profile in cases with greater symptomatic improvement, suggesting an association between clinical change and ambivalence evolution in therapy. Addressing ambivalence may bring to light important aspects of client's self-reconstruction after a major loss.